Scalp hair cortisol for diagnosis of Cushing's syndrome. Issue 6 (June 2017) - Wester, Vincent L; Reincke, Martin; Koper, Jan W; van den Akker, Erica L T; Manenschijn, Laura; Berr, Christina M; Fazel, Julia; de Rijke, Yolanda B; Feelders, Richard A; van Rossum, Elisabeth F C
Abstract : Objective: Current first-line screening tests for Cushing's syndrome (CS) only measure time-point or short-term cortisol. Hair cortisol content (HCC) offers a non-invasive way to measure long-term cortisol exposure over several months of time. We aimed to evaluate HCC as a screening tool for CS. Design: Case-control study in two academic referral centers for CS. Methods: Between 2009 and 2016, we collected scalp hair from patients suspected of CS and healthy controls. HCC was measured using ELISA. HCC was available in 43 confirmed CS patients, 35 patients in whom the diagnosis CS was rejected during diagnostic work-up and follow-up (patient controls), and 174 healthy controls. Additionally, we created HCC timelines in two patients with ectopic CS. Results: CS patients had higher HCC than patient controls and healthy controls (geometric mean 106.9 vs 12.7 and 8.4 pg/mg respectively, P < 0.001). At a cut-off of 31.1 pg/mg, HCC could differentiate between CS patients and healthy controls with a sensitivity of 93% and a specificity of 90%. With patient controls as a reference, specificity remained the same (91%). Within CS patients, HCC correlated significantly with urinary free cortisol ( r = 0.691, P < 0.001). In two ectopic CS patients, HCC timelines indicated that cortisol was increased 3 and 6 months before CS became clinically apparent. Conclusions: Analysis of cortisol in a single scalp hair sample offers diagnostic accuracy for CS similar to currently used first-line tests, and can be used to investigate cortisol exposure in CS patients months to years back in time, enabling the estimation of disease onset.